The costs of recruiting apprentices : evidence from German workplace-level data - Wenzelmann, Felix [Verfasser]; Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2017)
"In this article, we use workplace-level data to analyse the costs of filling an apprenticeship vacancy in Germany. We find that such recruitment costs amount on average to €600 per hire (almost one month's pay of an apprentice or approximately 1-2 % of a workplace's training expenditures), but costs are heterogeneous across workplaces and vary strongly by training occupation. Our results suggest that a high degree of competition among training workplaces in the region is associated with an increase in recruitment costs. Furthermore, we find that workplaces with a works council or an investment-oriented training strategy incur higher recruitment costs. Our results are important in light of the increasing competition for talented school leavers induced by demographic change." (Authors' abstract, BIBB-Doku)
Vorab veröffentlicht als Working Paper: (Leading House working paper ; 95). - http://repec.business.uzh.ch/RePEc/iso/leadinghouse/0095_lhwpaper.pdf [Zugriff 13.1.2017]
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 5.3 Personalentwicklung; S 4 Kosten & Finanzierung; G 1.2 Arbeitsmarkt; Betriebliche Berufsausbildung; Unbesetzte Ausbildungsplätze; Stellenbesetzung; Personalgewinnung; Kosten; Ausbildungsbetrieb; Ausbildungsinvestition; Einflussfaktor; Regionale Faktoren; Regionaler Arbeitsmarkt